Nacionalni preizkus znanja iz slovenščine ob zaključku srednje šole prve stopnje s slovenskim učnim jezikom v Italiji - Kaluža Pocecco, Tamara (Revija za elementarno izobraževanje, 2016)
The National Examination of Slovene Language at the End of Secondary School of the First Degree with Slovene as the Language of Instruction in Italy. National examinations were introduced in European countries in order to increase the efficiency and effectiveness of education. In Italy they have been carried out since 2007. The knowledge of Italian language or other first language (Slovene language in schools with Slovene as the language of instruction) and mathematics is checked. The paper presents the organization and the progress of national examinations in Italy and a detailed examination of the knowledge of Slovene language at the end of the three-year lower secondary school with Slovene as the language of instruction, following a five-year primary school, which corresponds to the last triennium of the nine-year basic school in Slovenia. In particular the nature of the examination in the school year 2009/10 according to the individual components of communication competences, according to the different levels of cognitive complexity and type of tasks has been assessed. The survey has shown that in the examination closed-type tasks predominate, with which simpler cognitive processes are verified.